Listeria monocytogenes induces host DNA damage and delays the host cell cycle to promote infection - Leitão, E (2014)
Listeria monocytogenes (Lm) is a human intracellular pathogen widely used to uncover the mechanisms evolved by pathogens to establish infection. However, its capacity to perturb the host cell cycle was never reported. We show that Lm infection affects the host cell cycle progression, increasing its overall duration but allowing consecutive rounds of division. A complete Lm infectious cycle induces a S-phase delay accompanied by a slower rate of DNA synthesis and increased levels of host DNA strand breaks. Additionally, DNA damage/replication checkpoint responses are triggered in an Lm dose-dependent manner through the phosphorylation of DNA-PK, H2A.X, and CDC25A and independently from ATM/ATR. While host DNA damage induced exogenously favors Lm dissemination, the override of checkpoint pathways limits infection. We propose that host DNA replication disturbed by Lm infection culminates in DNA strand breaks, triggering DNA damage/replication responses, and ensuring a cell cycle delay that favors Lm propagation.